PENGARUH PERPUTARAN KAS, PIUTANG DAN PERSEDIAAN TERHADAP RETURN ON ASSETS (ROA) PADA PT FAST FOOD INDONESIA TBK (Studi Kasus Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Meta Sulastia; Wardhani Indah Sari; Azwar (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
This study aims to test cash turnover, accounts receivable and inventory of return on assets at PT Fast Food Indonesia Tbk. This research method uses a quantitative descriptive method with a sample of financial statements of PT Fast Food Indonesia Tbk for the period 2008-2015. Analysis using multiple linear regression with the help of SPSS windows 23.0. Based on the results of the research partially, the variable cash turnover, accounts receivable and inventory have a significant influence on Return On Assets (ROA) at PT Fast Food Indonesia Tbk because it has tcount<ttable. Based on the results of the F test analysis, it is known that all independent variables (cash turnover, accounts receivable and inventory) have a simultaneous or joint effect on return on assets so that the decisions taken are Ho rejected and Ha accepted. The calculation of the Determination Coefficient (R2), can be concluded that the independent variables in this study have an Adjusted R Square value of 0.702 or 70.2%, this indicates that the percentage contribution of the influence of independent variables, namely cash turnover, accounts receivable and inventory can contributing influence of 70.2% on the dependent variable, namely Return On Assets (ROA). While the remaining 29.8% is influenced by other variables not included in this research model.